Integrasi Pendidikan Karakter Nasionalisme pada Mata Pelajaran PKn di SDN Tlogosari 01 - Eka Yulia Nabila Syaputri (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to analyze the integration of nationalism character education in Civics Education (PKn) at SDN Tlogosari 01 and identify the supporting and inhibiting factors. Using a qualitative case study approach, data were collected through observations, interviews, and documentation involving the principal, PKn teachers, and students from grades IV-VI. The findings reveal that PKn teachers integrate nationalism values through discussions, historical videos, and lessons on citizens' rights and responsibilities. School policies, such as flag ceremonies and nationalism-themed competitions, strengthen character education. However, challenges include teachers' limited understanding of value-based teaching strategies, lack of role models, and inadequate learning facilities. Key supporting factors are teacher commitment, parental involvement, and nationalism-themed extracurricular activities. The study recommends improving teachers' skills in innovative teaching methods and enhancing facilities to better internalize nationalism values, contributing to the development of character education in primary schools.